Studi Kasus: Implementasi Digital Governance dan Dampaknya terhadap Kinerja Organisasi Publik - Dede, Dede Azka ZM; Heri, Heri (Jurnal Intelek Insan Cendikia, 2024)
Developing an Electronic-Based Government System or e-Government is now a priority program for the government, not only to improve the quality of public services, but also to accelerate the management system of the State Civil Apparatus in Indonesia. When steps in e-government are equipped with participation and feedback, government officials will perceive the procedures as fair because of their ability to express their views and opinions. When people understand the results obtained according to their performance, government officials are in a better position to participate in the process of target setting, feedback, and correcting unfair performance evaluation decisions. Digital governance is a concept that refers to the application of information and communication technology (ICT) or ICT in the management and administration of government. By understanding this broad scope, the government can develop a holistic strategy to improve service quality and responsiveness to community needs. One of the main principles is openness, which emphasizes the importance of open access to public information and community participation in the decision-making process.Developing an Electronic-Based Government System or e-Government is now a priority program for the government, not only to improve the quality of public services, but also to accelerate the management system of the State Civil Apparatus in Indonesia. When steps in e-government are equipped with participation and feedback, government officials will perceive the procedures as fair because of their ability to express their views and opinions. When people understand the results obtained according to their performance, government officials are in a better position to participate in the process of target setting, feedback, and correcting unfair performance evaluation decisions. Digital governance is a concept that refers to the application of information and communication technology (ICT) or ICT in the management and administration of government. By understanding this broad scope, the government can develop a holistic strategy to improve service quality and responsiveness to community needs. One of the main principles is openness, which emphasizes the importance of open access to public information and community participation in the decision-making process.